2016
DOI: 10.1371/journal.pone.0153566
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic Nervous System Dysfunction, as Identified by Pupil Light Reflex, and Its Possible Connection to Hearing Impairment

Abstract: ContextAlthough the pupil light reflex has been widely used as a clinical diagnostic tool for autonomic nervous system dysfunction, there is no systematic review available to summarize the evidence that the pupil light reflex is a sensitive method to detect parasympathetic dysfunction. Meanwhile, the relationship between parasympathetic functioning and hearing impairment is relatively unknown.ObjectivesTo 1) review the evidence for the pupil light reflex being a sensitive method to evaluate parasympathetic dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 89 publications
(139 reference statements)
3
76
1
2
Order By: Relevance
“…This is also consistent with a key role for ACh in supporting attentive listening by suppressing distractorsa main feature of the present task (Berry et al, 2014;Demeter and Sarter, 2013;Himmelheber et al, 2000;Kim et al, 2017;Sarter et al, 2006). Future work with more sensitive techniques in animal models or pharmacological manipulations in humans (see also Steinhauer et al, 2004;Wang et al, 2016) is needed to tease apart the contribution of ACh and NE to attentive listening.…”
Section: Neuromodulator Effects On Sustained Attentionsupporting
confidence: 88%
“…This is also consistent with a key role for ACh in supporting attentive listening by suppressing distractorsa main feature of the present task (Berry et al, 2014;Demeter and Sarter, 2013;Himmelheber et al, 2000;Kim et al, 2017;Sarter et al, 2006). Future work with more sensitive techniques in animal models or pharmacological manipulations in humans (see also Steinhauer et al, 2004;Wang et al, 2016) is needed to tease apart the contribution of ACh and NE to attentive listening.…”
Section: Neuromodulator Effects On Sustained Attentionsupporting
confidence: 88%
“…While considerable experimental evidence linking locus coeruleus activity and pupil size has been reported (de Gee et al, ; Joshi et al, ; Murphy, O'Connell, O'Sullivan, Robertson, & Balsters, ; Rajkowski, Kubiak, & Aston‐Jones, ; Reimer et al, ; Varazzani et al, ), however, it is also possible that the cholinergic system exerts control over pupil size in visuo‐motor tasks (McGinley et al, ; Naber, Frässle, et al, ; Naber et al, ; Nelson & Mooney, ; Nieuwenhuis, de Geus, & Aston‐Jones, ; Reimer et al, ; Vinck et al, ). Changes in pupil size in response to task difficulty or explorative behavior in visual and auditory paradigms have previously been attributed to processes in the cholinergic, parasympathetic pathway including the Edinger‐Westphal nucleus rather than the adrenergic, sympathetic pathway (Steinhauer, Siegle, Condray, & Pless, ; Wang et al, ). Importantly, we also recently demonstrated that administration of choline supplementation, which likely boosts systemic cholinergic availability, both decreases resting pupil size and changes behavior toward a greater emphasis on accuracy rather than speed on precisely the same motor aiming task used presently (Naber et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Significant associations between compounds grouped by principal component analysis and obese asthma, current respiratory symptoms, obesity and body composition were also observed, even for low levels of EDCs exposure. Furthermore, our results showed that exposure to individual or combined EDCs is associated with changes in the ANS, specifically parasympathetic dysautonomia assessed through pupillometry, thus suggesting that EDCs may increase parasympathetic activity, resulting in a subsequent increase in the risk of asthma and obesity.…”
Section: Discussionmentioning
confidence: 68%